Machiavellianism in Cyberlaw: An In-Depth Analysis - Bagaskara, Tegar Christianto; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This study extracted data from Lens.org using "Cyberlaw OR Cyber Law" combined with "Machiavellianism" as keywords, focusing on journal articles within the legal domain. The objective was to investigate the intricate relationship between Machiavellianism and Cyberlaw, employing advanced search techniques. Results revealed a complex interplay between Machiavellian tendencies and legal strategies in cyberspace, emphasizing manipulative tactics within the digital legal landscape. This exploration holds profound implications, illuminating the behavioral dynamics in cyber legal contexts and offering insights for future research and policy formulation in the global legal arena.Highlights : Complex Relationship Unveiled: Reveals the interplay between Machiavellianism and Cyberlaw. Manipulative Tactics Highlighted: Emphasizes the use of manipulative strategies within the digital legal sphere. Implications for Policy and Research: Offers insights for future policy formulation and research in global legal contexts. Keywords: Cyberlaw, Machiavellianism, Legal Strategies, Manipulative Tactics, Behavioral Dynamics